2011
DOI: 10.3892/mmr.2011.551
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in estrogen receptor-α are associated with idiopathic female infertility

Abstract: Abstract. To investigate the relationship between polymorphisms in the estrogen receptor-α (ERα) gene and unexplained female infertility, restriction fragment length polymorphism (RFLP) analysis of ERα was employed in 150 females with idiopathic infertility (study group) and 150 healthy, age-matched females of proven fertility (control group). The results showed that the ERα allele frequencies differed significantly between the study and control groups (P=0.001). The allele identified by PvuII (P) restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Du et al reported Erα polymorphisms in UI vs fertile controls [ 90 ]. Significant differences in 4 different Erα allele frequencies were found between the two groups ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Du et al reported Erα polymorphisms in UI vs fertile controls [ 90 ]. Significant differences in 4 different Erα allele frequencies were found between the two groups ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that polymorphisms in the genes encoding aromatase (CYP19A1), hyaluronanbinding protein 2 and tissue factor pathway inhibitor could influence their levels of expression in receptive endometrium (Altmae et al, 2009(Altmae et al, , 2011a). Associations of polymorphisms in genes encoding anti-Müllerian hormone and its receptor, estrogen receptor alpha and leukemia inhibitory factor with unexplained infertility have also been reported (Steck et al, 2004;Rigon et al, 2010;Du et al, 2011). Many association studies have been performed in a search for molecular markers for recurrent miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Other study in relation to unexplained female infertility detected the P allele of PvuII polymorphism as a risk factor for females' idiopathic infertility, whereas X allele of XbaI had been reported to play a protective role regarding this condition [27]. …”
Section: Discussionmentioning
confidence: 99%